Effects of stabilized stannous fluoride dentifrice on dental calculus, dental plaque, gingivitis, halitosis and stain: A systematic review. Issue 12 (December 2019) - Johannsen, A.; Emilson, C.-G.; Johannsen, G.; Konradsson, K.; Lingström, P.; Ramberg, P.
Abstract: Objectives: The aim of the present systematic review was to examine the scientific evidence for the efficacy of stabilized stannous fluoride (SnF2 ) dentifrice in relation to dental calculus, dental plaque, gingivitis, halitosis and staining. Data and sources: Medline OVID, Embase.com, and the Cochrane Library were searched from database inception until June 2017. Six researchers independently selected studies, extracted data, and assessed methodological quality. A meta-analysis of the 6-month gingivitis studies was done. Risk of bias was estimated using a checklist from the Swedish Agency for Health Technology Assessment (SBU, 2018). Study selection: Two studies on dental calculus, 21 on dental plaque and gingivitis, 4 on halitosis, and 5 on stain met the inclusion criteria. Risk of bias was high for the studies on dental calculus, halitosis, and stain, and varied for the dental plaque and gingivitis studies. Significant reductions in dental calculus and in halitosis were reported for the SnF2 dentifrice; no differences in stain reduction were noted. A meta-analysis on gingivitis found better results for the SnF2 dentifrice compared to other dentifrices, though the results of the individual trials in the meta-analyses showed a substantial heterogeneity. Conclusions: The present review found that stabilized SnF2 toothpaste had a positive effect on the reduction of dental calculus build-up, dental plaque, gingivitis, stain and halitosis. A tendency towards a more pronounced effect than using toothpastes not containing SnF2 was found. However, a new generation of well conducted randomized trials are needed to further support these findings. Clinical relevance: Adding a SnF2 toothpaste to the daily oral care routine is an easy strategy that may have multiple oral health benefits. Abstract : Dentistry; Stabilized stannous fluoride; Dental calculus; Dental plaque; Gingivitis; Halitosis; Stain.